PEMULIHARAAN ARTIFAK DI MUZIUM NEGERI TERENGGANU - NOOR SULAINI, HUSSIN (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This study aims to determine the methods of conservation of artefacts in Terengganu State Museum, documenting the types of artifacts and methods used for conservation, thus analyzing the effectiveness of the conservation of artifacts. Qualitative Methods will help to identify the implementation of conservation and preservation of the theoretical and systematic approach to maximize the effectiveness of conservation units function museum.